A Comparative Study of the Oxygen Reduction Reaction on Pt and Ag in Alkaline Media - Alexander Rampf; Michael Braig; Stefano Passerini; Roswitha Zeis (ChemElectroChem)
Abstract Investigating the ORR under practical conditions is vital for optimizing metal–air batteries and alkaline fuel cells. Herein, we characterized Pt and Ag gas diffusion electrodes (GDE) in a GDE half‐cell in high alkaline concentrations at elevated temperatures by polarization curves and electrochemical impedance spectroscopy (EIS) combined with the distribution of relaxation times (DRT) analysis. The Pt catalyst's polarization curve displays substantial losses below 0.82 V vs. RHE. The DRT analysis reveals significantly increased charge transfer resistance and a decelerated ORR at that potential. RRDE measurements attributed the polarization loss observed for Pt catalysts to increased peroxide formation in this potential region triggered by the desorption of oxygenated species. Therefore, the ORR activity of Ag exceeds some of the here‐used Pt catalysts at high current densities. This work combines the benefits of the RRDE and the GDE half‐cell to study catalysts and identify the reaction mechanisms under conditions relevant to practical fuel cells and batteries. Moreover, the DRT analysis is introduced as an analytical tool to determine the charge transfer resistance contribution and the corresponding frequency of the ORR.